2015
DOI: 10.1002/2015gl063107
|View full text |Cite
|
Sign up to set email alerts
|

Rupture termination at restraining bends: The last great earthquake on the Altyn Tagh Fault

Abstract: Strike‐slip rupture propagation falters where changes in fault strike increase Coulomb failure stress. Numerical models of this phenomenon offer predictions of rupture extent based on bend geometry, but have not been verified with field data. To test model predictions of rupture barriers, we examine rupture extent along a section of the sinistral Altyn Tagh Fault punctuated by three major double bends. We measure 3–8 m offsets and map >95 km of continuous scarps that define the most recent surface rupture. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 41 publications
4
50
0
Order By: Relevance
“…To quantify the earthquake magnitudes implied by a scenario of clustered earthquakes, we use AD values of 3 and 5 m to infer that between 2 and 8 > Mw 7.5 earthquakes are needed to accrue the 7-23 m of total slip during the pulse (Table 2). These AD values are consistent with slip distributions interpreted to result from the most recent earthquake (MRE) along the Cherchen He and Qing Shui Quan section of the ATF (Muretta, 2009), and are similar to those seen on fault sections farther east (Elliott et al, 2015;Washburn et al, 2003). Use of these MRE slip values assumes that surface displacement has remained roughly constant from earthquake to earthquake, although the pacing of those events may have varied in time.…”
Section: Earthquake Clustersupporting
confidence: 84%
“…To quantify the earthquake magnitudes implied by a scenario of clustered earthquakes, we use AD values of 3 and 5 m to infer that between 2 and 8 > Mw 7.5 earthquakes are needed to accrue the 7-23 m of total slip during the pulse (Table 2). These AD values are consistent with slip distributions interpreted to result from the most recent earthquake (MRE) along the Cherchen He and Qing Shui Quan section of the ATF (Muretta, 2009), and are similar to those seen on fault sections farther east (Elliott et al, 2015;Washburn et al, 2003). Use of these MRE slip values assumes that surface displacement has remained roughly constant from earthquake to earthquake, although the pacing of those events may have varied in time.…”
Section: Earthquake Clustersupporting
confidence: 84%
“…It has been proposed that gradients in strike-slip motion may be absorbed by adjacent crustal thickening [Kirby et al, 2007;Selander et al, 2012]. Within the Aksay Bend, the ATF also acts as the root of neighboring thrust or oblique-slip faults that uplift the Altyn Tagh Ranges, absorbing deformation as slip decreases on the main SATF strand to near zero [Elliott et al, 2015]. Within the Aksay Bend, the ATF also acts as the root of neighboring thrust or oblique-slip faults that uplift the Altyn Tagh Ranges, absorbing deformation as slip decreases on the main SATF strand to near zero [Elliott et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The bend includes two major subparallel strike-slip faults: the Northern Altyn Tagh Fault (NATF) and the Southern Altyn Tagh Fault (SATF). The strike-slip activity on the SATF was proposed as ending within the bend [Elliott et al, 2015], though the trace of the SATF continues toward the east until it bends southeastward and disappears within the Nanshan area of the Qilian Shan Ranges [Mériaux et al, 2004]. The SATF continues as the main active trace to the west, whereas the NATF becomes the main active trace to the east (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This geometrical complexity can play a controlling role in the nucleation and propagation of earthquakes [Kase and Day, 2006;Avouac et al, 2014]. Studies from many historical surface ruptures [Wesnousky, 2006;Elliott et al, 2015] and dynamic modeling [e.g., Harris and Day, 1999;Kase and Day, 2006;Lozos et al, 2012] have suggested that large stepovers (≥3-4 km wide) are likely to arrest seismic ruptures. Furthermore, many small-scale complexities such as variations in strike and dip of fault segments within a stepover may also have an influence on rupture processes [Lozos et al, 2012].…”
Section: Introductionmentioning
confidence: 99%